Formulae are rearranged and solved. The solution is detailed and well presented. The response received a rating of "5/5" from the student who originally posted the question.

... But we have to solve the inhomogeneous equation (*) due to the ... The equation (*) is d 2v dv 20 × 10 × 1 × 10 ... 3 −6 + v = 40 × 0.35 dt dt Rearrange we have ...

Application Word Problems : Fractions, Ratio and Proportion, Perimeter of Triangle and Rearranging Formulas. ... of hot tap water at 70°C by solving the equation. ...

... 8. 24x+12y=-7 -----1) 16x-19=18y On rearranging, we get 16x ... 78y=71 y=-(71/78) Put y=-(71/78) in equation (1), we ... x=51/(78*4)=17/(26*4)=17/104 Solution is (17 ...

... your solution leads to the following equation for v(t) which satisfies the stated initial condition: (aV0 + b)/V0 exp (bt) = (av(t) + b)/ v(t) f. Rearrange...

... We'll rearrange this in the form y = mx + b 2) 8 ... the 1st equation to the y in the first equation, we will have: [3x + y = 1](− 2) 6x + y = 2 Solving, we have ...

... STEP 4: Algebraic manipulation to find an equation for v2. ... Finally rearranging (11) to make v2 the subject we get an ... The problem is then solved on this basis by ...

...Rearrange the equation, x+3 +2 ... 0 x x +1 ≤0 x Case 1: x+1 ≤ 0 and x >0, When x+ 1 ≤ 0, x ≤ -1. At the same time x >0. So there is no solution in this ...

... of Mordell's equation to prove that the stated equation has no ... Suppose to the contrary that an integer solution (x,y) exists. ... By rearranging terms one can write. ...

... 2. Use integrating factor to convert the following equation into "exact ODE" form and solve for y. 2 xy ' = ( y − x )( y + x ) / y Rearrange the equation ...